Leveraging CRISPR Cas9 RNPs and Cre-loxP in Picochlorum celeri for generation of field deployable strains and selection marker recycling - Burch, Tyson A.; Krishnan, Anagha; Posewitz, Matthew C. (Frontiers in Microbiology, 2025)
As new highly productive strains of algae are discovered and developed to meet the energy, chemical, and food requirements of the future, genetic engineering of those strains in a manner that yields deployable transformants is paramount. This study introduces the novel CRoxP (Cas9 RNPs coupled with an inducible CRe-loxP) system for rapid generation of marker- and transgene-free strains of Picochlorum celeri. The CRoxP system allows reuse of selection markers without Cas9 expression in vivo, eliminating many of the bottlenecks associated with conventional CRISPR Cas9 use for precise genome editing. In P. celeri, transformants were generated with a turnaround time as short as 21 days between transformation and being ready for another round of transformation with the same selection marker by using the CRoxP system. As a use-case for CRoxP, depigmented strains of P. celeri were generated by multiplexed Cas9 disruption of major LHCII genes followed by either a second round of LHCII targeting, or knockout of an LHCI gene. One transformant tested in flask culture (R6) exhibited similar biomass production to the wild type with 46% less Chl a + b on a biomass basis. In photobioreactors and under diel light simulating a solar day, a transformant (LhcBM31) exhibited 34 g AFDW m–2 d–1 with 54% less Chl a + b on a biomass basis vs. wild type.